2021
DOI: 10.3389/fped.2021.651544
|View full text |Cite
|
Sign up to set email alerts
|

Function of miR-24 and miR-27 in Pediatric Patients With Idiopathic Nephrotic Syndrome

Abstract: Purpose: We investigated the pathogenesis of idiopathic nephrotic syndrome (INS) by measuring the effects two specific miRNAs on Th2 cells in children with this disease.Methods: After informed consent, we enrolled 20 children with active INS before steroid initiation, 20 children with INS in remission after steroid therapy, and 20 age-matched healthy controls. Flow cytometry was used to measure the levels of Th2 cells and a cytometric bead array was used to measure the levels of IgE, interleukin (IL)−4, and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In our study, the median serum IgE was significantly higher in group I (275.55IU/ml) than group II (100.5IU/ml). Our results were matched with Ni et al (6) , who reported that analysis of IgE concentration indicated significantly greater levels in the active phase (firstonset) group with atopic constitution (1350.67 ± 837.39 IU/mL, p < 0.05) and the active phase group with non-atopic constitution (441.01 ± 357.45 IU/mL, p < 0.05) than in the control group (57.76 ± 48.25 IU/mL). Also, Hossain (7) , reported that the mean serum IgE level of nephrotic syndrome in children was (537.98±52.56IU/ml) which was higher than controls (38 ± 18 kU/L), p (<0.05).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the median serum IgE was significantly higher in group I (275.55IU/ml) than group II (100.5IU/ml). Our results were matched with Ni et al (6) , who reported that analysis of IgE concentration indicated significantly greater levels in the active phase (firstonset) group with atopic constitution (1350.67 ± 837.39 IU/mL, p < 0.05) and the active phase group with non-atopic constitution (441.01 ± 357.45 IU/mL, p < 0.05) than in the control group (57.76 ± 48.25 IU/mL). Also, Hossain (7) , reported that the mean serum IgE level of nephrotic syndrome in children was (537.98±52.56IU/ml) which was higher than controls (38 ± 18 kU/L), p (<0.05).…”
Section: Discussionsupporting
confidence: 93%
“…Though there were no significant differences in the history of allergy between the low- and high-IgE groups in this study, a higher percentage of eosinophilia was observed in the high-IgE group, indicating that the allergic condition may exist. Ni et al ( 20 ) and Cheung et al ( 21 ) reported that serum IgE levels of MCD patients were higher in the atopic subgroup than that in the non-atopic subgroup at the time of remission. We assessed the IgE levels when patients were in remission.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the increase in serum IgE levels might be related to Th2 activation ( 29 , 30 ). Some evidence suggests that the Th2 cytokine, IL-13, may play a potential regulatory role in MCD pathogenesis and high serum IgE levels: multiple reports have shown that serum IL-13 levels in MCD patients are elevated; IL-13 can regulate IgE production; and IL-13 can induce glomerular podocyte damage in animal models and caused MCD-like pathological changes ( 11 , 20 , 21 ). Therefore, IL-13 may drive the onset of the nephrotic syndrome and the increase of serum IgE levels.…”
Section: Discussionmentioning
confidence: 99%